Social vulnerability and asthma-related emergency medical services in Illinois - Geiger, Sarah Dee; Khaium, M. Omar; Gustafson, Evan M.; Shapiro, Marcus; Keeley, Sarah; Johnson, Cassandra; Amerson, Nancy; Lee, Daniel; Gerald, Lynn B.; Keddie, Arlene (Frontiers in Public Health, 2025)
IntroductionThis ecologic study explores the relationship between the Social Vulnerability Index (SVI) and probable asthma-related emergency medical service (EMS) rates before and during the COVID-19 pandemic at the county level in Illinois.MethodsThe number of asthma-related EMS visits was obtained in all 102 counties for adults aged 18 years or more, and for 82 of these counties for children aged less than 18 from 2018 to 2021. They were converted into rates and examined in relation to SVI rankings. Pearson’s correlation coefficients and negative binomial regression were used to examine associations, adjusting for the level of rurality.ResultsThe rate of asthma-related EMS visits increased in adults from 23.1 to 28.9 per 1,000 between 2018 and 2021 but decreased in children from 5.9 to 5 per 1,000. Every 1% increase in the overall SVI was associated with a nearly two-fold increase in the rate of EMS visits in adults (pre-COVID-19: IRR = 1.94, p < 0.01; during-COVID: IRR = 1.90, p < 0.01) and an even greater increase in children (pre-COVID-19: IRR = 2.61, p < 0.01; during-COVID: IRR = 2.92, p < 0.01) Consistent associations were found for the SVI themes of socioeconomic status, housing type, and transportation across age groups and time periods.DiscussionDuring the pandemic, all four themes of SVI were associated with the asthma EMS rate in children. This study has shown that the same factors that lead to community vulnerability in a disaster align with a greater need for on-site asthma emergency treatment.